Screening of gram-positive opportunistic bacteria from oral cancer infection and their antibiotic resistance pattern - Eva, Farzana Rahman (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.